Predicting Special Educators' Intent to Continue Teaching Students with Emotional or Behavioral Disorders in Self-Contained Settings. (January 2020) - Bettini, Elizabeth; Cumming, Michelle M.; O'Brien, Kristen Merrill; Brunsting, Nelson C.; Ragunathan, Maalavika; Sutton, Rachel; Chopra, Akash
Schools experience difficulty retaining special educators to serve students with emotional or behavioral disorders (EBD) in self-contained settings, as they have higher rates of burnout and attrition than other educators. Administrators could prevent these outcomes by improving working conditions, but research provides limited insights into which conditions are most important for these special educators. Using structural equation modeling to analyze data from a national survey, we found that special educators' perceptions of adequacy of planning time, workload manageability, stress, and emotional exhaustion mediated relationships between other working conditions and intent to stay. Specifically, special educators who reported that they (a) spent more time planning outside school (b) supervised more paraprofessionals, (c) had limited access to curricular resources, and (d) served more heterogeneous instructional groups were more likely to report having insufficient planning time, unmanageable workloads, stress, emotional exhaustion, and intent to leave. Results imply that administrators should target planning time, curricular resources, and instructional grouping.